2008
DOI: 10.4319/lo.2008.53.2.0705
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient biogeochemistry in a Gulf of Mexico subterranean estuary and groundwater‐derived fluxes to the coastal ocean

Abstract: We hypothesize that biogeochemical processes in a subterranean estuary in the northeastern Gulf of Mexico significantly alter nutrient concentrations that are discharged into the ocean via submarine groundwater discharge (SGD). This subterranean estuary is a site of steep gradients over small spatial scales, so selecting the appropriate groundwater endmember for flux calculations is difficult. Two-endmember mixing models typically applied to investigate biogeochemical processes in surface estuaries are not use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
151
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 53 publications
5
151
2
5
Order By: Relevance
“…For instance, a study by Addy et al (2005) showed that mixing between the organic-matter-rich seawater and the nutrientrich fresh groundwater increased the denitrification capacity in the STE below a Rhode Island fringing salt marsh. Santos et al (2008) found that re-circulated SGD drives oxic re-mineralization and de-nitrification in the STE of the Gulf of Mexico. However, the active biogeochemical transformations in the STE do not always take place.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, a study by Addy et al (2005) showed that mixing between the organic-matter-rich seawater and the nutrientrich fresh groundwater increased the denitrification capacity in the STE below a Rhode Island fringing salt marsh. Santos et al (2008) found that re-circulated SGD drives oxic re-mineralization and de-nitrification in the STE of the Gulf of Mexico. However, the active biogeochemical transformations in the STE do not always take place.…”
Section: Discussionmentioning
confidence: 97%
“…Submarine groundwater discharge (SGD) is well documented as an important source of inorganic, organic, and microbial pollutants to the coastal ocean (Boehm et al 2004;Bone et al 2007;Santos et al 2008). Numerous physical forcing mechanisms including meteoric hydraulic head, tide and wave pumping, seasonal precipitation/evapotranspiration cycles, and variations in groundwater density force the flow of groundwater to the ocean (Burnett et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these uncertainties, different local and regional studies demonstrate that SGDassociated fluxes of nutrients into the coastal ocean can be comparable to or even higher than the relatively better quantified river fluxes [Slomp and Van Cappellen, 2004;Santos et al, 2008]. Large scale estimates of SGD based on 228 Ra observations in large ocean basins are now available Kwon et al, 2014].…”
mentioning
confidence: 99%